Assessment of English Language Learning in 2013 Curriculum - Bulan, Arif; Suryaman, Maman; Nurhasanah, Enung; Mardiah, Mardiah; Hasan, Hasan (Universitas Malikussaleh, 2020)
This study aims to determine: (1) the implementation of the 2013 curriculum in the assessment of English learning conducted by teachers; (2) the implementation of the 2013 curriculum English learning assessment in terms of national examination results; (3) the implementation of the 2013 curriculum English learning assessment in terms of teacher stratum. This research is a survey research using a quantitative approach and supported by a qualitative approach. This research was conducted in 16 state high schools in Sleman Regency. The samples in this study were 34 English teachers, all of them had taught based on the 2013 curriculum. Data collection in this study used questionnaires, observations, document analysis and interviews. The data analysis technique used is quantitative and qualitative descriptive techniques. The results of this study indicate that: (1) the implementation of the 2013 curriculum in learning assessment gets an average score of 3.5 (very good). Learning assessment is carried out based on education assessment standards in the 2013 curriculum. (2) implementation of learning assessments that are in accordance with the 2013 curriculum in schools that have low, medium, and high national examination scores is included in the excellent category with an average percentage of 87.45%; (3) the implementation of learning assessment that is in accordance with the 2013 curriculum in terms of the stratum of teachers, that non-civil servant teachers implement higher learning assessment than civil servant teachers.